Level Of Schooling And Gender Differences In Test Anxiety Among Secondary School Students In Port Harcourt Local Government Area Of Rivers State - N., Onukwufor Jonathan; J., Ugwu Chinelo (Advances in Social Sciences Research Journal, 2018)
This research was conducted to ascertain the level of schooling and gender differences in secondary school students’ test anxiety. The study was carried out in Port Harcourt Local Government Area of Rivers State. The population of the study was made up of all the Junior Secondary School class two (JSS 2) students and all senior secondary school class two (SSS 2) students in Port Harcourt Local Government Area of Rivers State. Simple random sampling and stratified random sampling techniques were used to draw a sample of 308 students which comprised 108 JSS and 200 SSS 2 students. The sample was also made up of 136 females and 172 male students. The instrument used for the study was captioned Test Anxiety Inventory (TAI). The instrument was validated and Crombach Alpha was used to determine the reliability of the instrument and the reliability coefficient obtained was 0.75. Two research questions and two hypotheses guided the study. The findings of the study are as follows: There was significant difference between JSS and SSS students test anxiety. Senior secondary school students significantly had more text anxiety than Junior Secondary School students. There was significant difference between male and female students’ test anxiety in Port Harcourt Local Government Area of Rivers State. The female students significantly had more test anxiety than male students, some recommendations were made, which includes that teachers should prepare students adequately for any examination they are to write especially external examinations so as to instill great confidence in the students.